REGRESSION AND CORRELATION ANALYSIS STOCK PRICE WITH BANKRUPTCY (CASE STUDY WITH ZMIJEWSKI BANKRUPTCY MODEL) - Sugiarto, Teguh; Rahayu, Sri; Subagyo, Ahmad; Madu, Ludiro; Amiri, Amir Mohamadian (International Journal of Research -GRANTHAALAYAH, 2017)
The purpose of this study to determine how the correlation effect of corporate bankruptcies with stock prices. The study was conducted on companies in the ceramics, glass and porcelain sectors whose shares are traded on the Indonesia Stock Exchange and publish the financial statements in Indonesia Stock Exchange (BEI) in the period 2010-2014. The method used in this research is correlation and regression of OLS. From the research that has been done can be concluded that, the result of regression test of five models at the proposed quadratic value of R is very low and indicate the happening of spurious regression. Using hyposis made concluded that Model H0: βi = 0 regression is not significant, whereas correlation test on proposal received H0: βi ≠ 0 happened weak correlation between bankruptcy analysis with stock price.